Patio roses. Stem formation dynamics - I.L. Denysko (Інтродукція Рослин, 2010)
The results of the researches on stem formation dynamics of patio (miniflora) roses in the natural and climate conditions of Podilla-Transdnieperia country of the Forest-Steppe zone of Ukraine are reported. The calendar terms of intensive stem formation periods and their duration are identified.